1991
DOI: 10.1164/ajrccm/144.2.331
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Oropharyngeal Cultures for Identifying Lower Airway Bacteria in Cystic Fibrosis Patients

Abstract: Identifying lower respiratory pathogens in young, non expectorating cystic fibrosis (CF) patients has been problematic. Bronchial secretions are difficult to obtain, and little is known about lower airway flora in these patients. We collected simultaneous bronchial and oropharyngeal specimens in 43 CF patients in optimal respiratory status, including both expectorating (17) and nonexpectorating (26) patients, to determine the predictive value of oropharyngeal cultures for identifying lower airway pathogens. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
100
1
4

Year Published

1996
1996
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(114 citation statements)
references
References 9 publications
7
100
1
4
Order By: Relevance
“…The absence of the pathogen in the culture from the nasopharyngeal aspirate did not exclude the possibility that the pathogen occurred in the lower airways. This finding has also been observed by others [4]. However, the current authors found the ratio of negative Pseudomonas spp.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The absence of the pathogen in the culture from the nasopharyngeal aspirate did not exclude the possibility that the pathogen occurred in the lower airways. This finding has also been observed by others [4]. However, the current authors found the ratio of negative Pseudomonas spp.…”
Section: Discussionsupporting
confidence: 91%
“…However, the current authors found the ratio of negative Pseudomonas spp. cultures from the upper airways while positive from the lower to be higher than in studies mentioned previously [4,5]. The fact that a nasopharyngeal aspirate was evaluated whilst other studies have assessed an oropharyngeal swab may explain this difference.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…In non-expectorating patients oropharyngeal cultures yielding P. aeruginosa are highly predictive [25]. However, false-negative results from throat cultures may occur making additional diagnostic tools necessary.…”
Section: Diagnosis Of Pseudomonas Aeruginosa Lung Infectionmentioning
confidence: 99%
“…Alternatively a new approach of using preservative free tobramycin in a month on/month off fashion has been shown to be superior in terms of lung function than standard care in the USA (which included intravenous treatment on demand during exacerbations) [33]. Regardless of whether or not the patients experienced exacerbations for which they received intravenous antipseudomonal antibiotics, the FEV1 predicted of patients receiving placebo, decreased steadily during the pivotal trials [25]. The benefits to lung function observed following initiation of preservative free tobramycin therapy were similar among patients with and without symptoms requiring treatment with intravenous antipseudomonal antibiotics.…”
Section: Antibiotic Strategies Against Pseudomonas Aeruginosamentioning
confidence: 99%